The day Siti was battered - Reggie Dutt (Asia Pacific Network, 2001)
Sitiveni Moce, a 37-year-old Sun photojournalist, was beaten by rebels in the Fiji Parliament during the Speight coup crisis in full view of other media. Siti says he glad that none of his media colleagues tried to take pictures of him being assulated, or come to his rescue.